What drives network governance? A microstructural approach - Vizzoto, Andrieli Diniz (Universidade do Vale do Rio dos Sinos, 2023)
Collaborative networks development, as a competitive strategy and form to deal with complex society problems with many diverse members working towards common goals, have become recurrent. Although these configurations follow steady theories for organizations, they present particularities that need to be comprehended from a network perspective, considering its own uniqueness. Network governance as an organizational and planning tool needs studies that interpret it from downstream, examining the routine activities of governance in a processual way, micro governance. Besides, networks present a dichotomy between authority and autonomy, a space where members are interdependent, sometimes it is imperative that some authority acts to take decisions, mediate conflicts and control situations. Literature presents some theories yet not deep studied about network micro governance practices. Therefore, this study has aimed to understand the processes of micro governance that act as authority source and their role in the network governance. So, a qualitative research was held, using observation, documents analyses and interviews (17) with members of a public healthcare network in Brazil, Conass. Using a process data analysis, searching for patterns along time, the evidence was analyzed. The empirical field was chosen based on it dealing with a complex social problem, public health. The network was formed in 1982, and it has a large structure with technical chambers, commissions and committees that debate and take decisions on how to organize the capillary and budgetary issues towards results for public healthcare in the country. Thus, many activities and governance processes work, and these are the objects of this study. Among the results, it was evident that micro governance functions play a critical role so that the network performs. Some functions were more highlighted within the evidence such as align, organize, monitoring and arbitrate. Based on those, propositions were created for these network micro governance functions, revealing their applicability and enhancing the theories with empirical evidence. The results have shown that functions of align and organize help to balance expectations and offer continuity for the network, considering the constant possibility of entry and exit of members. The function of monitoring legitimizes the network governance processes, since it is used to control results and offer feedback about the goals. Also, the evidence conveys that the function arbitrate supports the collaborative environment promoting consensus, the way the network decides on how to conduct the decision process and solve conflicts. Finally, the network micro governance functions become part of the structure and depicts a reality by playing the role of authority. Consequently, no member or leadership role is responsible solemnly to emphasize or force no one in the network to use the micro governance functions, they work on their own. The evidence demonstrates that micro governance functions offer authority and authenticity to processes, fostering a collaborative and horizontal environment among network members.
Keywords: Funções de micro governança; Redes de colaboração; Autoridade; Problemas complexos; Micro governance functions; Collaborative networks; Authority; Complex problems; ACCNPQ::Ciências Sociais Aplicadas::Administração